Structure-guided optimization of small molecules targeting Yck2 as a strategy to combat Candida albicans - Emily Puumala; Meganathan Nandakumar; Bonnie Yiu; Peter J. Stogios; Benjamin G. Strickland; Robert Zarnowski; Xiaoyu Wang; Noelle S. Williams; Alexei Savchenko; David R. Andes; Nicole Robbins; Luke Whitesell; et al. (Nature Communications)
Abstract Candida albicans is the most common cause of life-threatening fungal infection in the developed world but remains a therapeutic challenge. Protein kinases have been rewarding drug targets across diverse indications but remain untapped for antifungal development. Previously, screening kinase inhibitors against C. albicans revealed a 2,3-aryl-pyrazolopyridine, GW461484A (GW), which targets casein kinase 1 (CK1) family member Yck2. Here, we report optimization of GW via two complementary approaches, synthesis of bioisosteres possessing an imidazo[1,2-a]pyridine core, and R-group substitution of GW’s pyrazolo[1,5-a]pyridine core. Characterization of compounds reveals two 6-cyano derivatives with improved pharmacological properties that retain whole-cell bioactivity and selectivity for fungal Yck2 compared to human CK1α. Efficacy studies in mice indicate both analogs possess single-agent activity against C. albicans resistant to first-line echinocandin antifungals and potentiate non-curative echinocandin treatment. Results validate Yck2 as an antifungal target and encourage further development of inhibitors acting by this previously unexploited mode of action.